One-dimensional simulation of a retrofitted medium duty engine running using compressed natural gas - Ismail, Muhammad Yusri (2014)
Environmental improvement and energy issues are recently becoming one of the worldwide concerns due to the increasing demand for petroleum usage especially from the automotive sector. This situation had lead to encounter for a new technology and reliable alternative fuel. A potential alternative fuel for compression ignition (C.I.) engine is the compressed natural gas (CNG). For C.I. engines to operate using CNG, or to be converted as a retrofitted CNG engine, further modifications are required. Previous works reported loss in brake power (BP) and increase in hydrocarbon (HC) emission for C.I. engine retrofitted with CNG fuelling. Analysis of performance and exhaust emissions characteristics for CNG retrofitted engine through experimental analysis requires high cost and very time consuming. Thus, a One –Dimensional simulation software, was introduced in this study to reduce the experimental process and setup. In this study a medium duty 4.3L, 4- cylinder, 4-stroke retrofitted compression ignition engine (RE) model were used in this simulation work over various operational conditions at low engine speed. At the beginning of this study, the model was first compared with a medium duty 4.3L, 4- cylinder, 4-stroke C.I. engine (DE) in order to predict the engine model capabilities running with different fuel types at low speed condition. The most significant finding in this simulation configuration is the RE model was able to reduce the fuel consumption (BSFC) and experience lower; brake power (BP), brake torque (BT) and brake thermal efficiency (BTE) by 18.1%, 30.3%, 30.7%, and 14.6% respectively. For emissions results the model generated higher unburned hydrocarbon emissions (HC) and lower; oxides of nitrogen (NOx), carbon dioxides (CO2) and carbon monoxides (CO) by 99%, 60.2%, 56.4% and 36.1% respectively. The model also had been tested at various air-fuel ratio (AFR) condition varies from 15 (rich), 17.2 (stoichiometric) and 19 (lean) condition. Finally the comparison between the simulation model and experimental engine results for performance and emissions characteristics at low engine speed are presented, and it is confirmed that the result in this study able to produce a roughly similar trend.